Analisa Perancangan Desain Kemasan Minuman Di Ukm Panggon Ngombe Dengan Metode Kansei Engineering - Ratmojo, M. Affandi; Hasibuan, Chalis Fajri; Polewangi, Yudi Daeng (Universitas Medan Area, 2022)
UKM (Small-Medium Business) Panggon Ngombe is one of the Small-Medium Businesses in Medan that produces Beverages. The processed product from UKM Panggon Ngombe is Boba Drink. UKM Panggon Ngombe has problems in marketing their products; one of the reasons is the unattractive product packaging and still not following customer needs. This study aimed to produce Kansei words that were priorities for beverage packaging improvements, to determine the importance of items affected consumer tastes, and to produce packaging category specifications and beverage packaging designs by using the Kansei Engineering method. Kansei Engineering is defined as a methodology to translate human psychological processes towards the expected product design, by defining consumers' expectations identified through Kansei words into product design. The sample used in the study used a survey method, it was a way of taking a sample with a questionnaire as a research tool in a population, and only 100 respondents were studied, so the conclusions showed were limited to objects. The results of the study produced Kansei words luxury, informative, aesthetic appearance, durable, practical, attractive, and hygienic. The importance level of the items obtained 7 Kansei words for bottle packaging, 6 Kansei words for plastic packaging materials, 7 Kansei words for brown and black packaging colors, 6 Kansei words for 600 ml packaging size, 7 Kansei words for packaging information, 7 Kansei words for circle logo shape, 7 Kansei words for comic san MS writing type, 7 Kansei words for yellow and white packaging writing colors, and 6 Kansei words for boba images on packaging. Specifications for beverage packaging in the bottles form with plastic packaging materials, brown and black packaging colors, packaging sizes 600 ml, yellow and white writing colors, circle logo shape, product information, and boba picture.